PEMANFAATAN LIMBAH PLASTIK SIMPUL SEBAGAI PENGGANTI AGREGAT KASAR PADA BETON - Mohtarom Riyadi; Mohammad Hadiyat Rizkin; Zakaria Ramadhan (Politeknik Negeri Jakarta, 2015)
Abstract HDPE or High Density Polyethylene is a type of white plastic milk / white. Used for pocket tissue, detergent bottles, oil, anti-heat plastic, plastic pipes, plastic shopping bag and a regular bag for vegetable food as flexible with high strength. This plastic is non-degregdable, so it needs special attention to handle these types of plastic waste. Therefore, in this study used HDPE plastic waste created node types to be used as a substitute for gravel coarse aggregate in concrete. The study was conducted on concrete with coarse aggregate to subtitude made from waste plastic bags made of HDPE node types with higher levels of 0%, 50% and 100% of the volume of broken stone. Mix proportions used is the ratio of volume 1 PC: 2 Fine aggregate: 2 coarse aggregate. Analysis on testing coarse aggregate made from waste plastic bags made of HDPE knot types obtained specific gravity of 0.570, loose bulk density of 0.24 gram/cm3 and solid content of 0.3 weight gram/cm3. The aggregate categorized as mild as it has a specific gravity by BJ